Proteomic analysis of synergetic neuroprotective effect of adenosine, thiamine, niacin and cyanocobalamin in pathophysiology of diabetic polyneuropathy - O. A. Gromova; I. Yu. Torshin; A. G. Moiseenok (Фармакоэкономика)
Background. Neurotransmitter adenosine and B-group vitamins have neuroprotective, remyelinizing and anti-neuroinflammatory properties. Despite the studies of these molecules for decades, the molecular mechanisms of their synergistic effect on neuroinflammation processes are unexplored and not systematized.Objective: to establish the molecular mechanisms of synergism of adenosine, thiamine, niacin and cyanocobalamin in counteracting the pathology of diabetic polyneuropathy (DPN).Material and methods. The molecular mechanisms of action of adenosine, thiamine (vitamin B1), niacin (vitamin PP) and cyanocobalamin (vitamin B12) in the pathophysiology of DPN were determined using functional analysis of genomic and proteomic databases.Results. The analysis of 20,180 annotated proteins of the human proteome identified 504 vitamin-PP-dependent, 22 vitamin-B1-dependent, 24 vitamin-B12-dependent and 50 adenosine-dependent proteins. The proteins of the human proteome were detected, the activity or levels of which are important for reducing neuroinflammation, remyelination, neurogenesis, biosynthesis of neuronal adenosine triphosphate, myelin homeostasis, neuroplasticity, neutralization of homocysteine, regeneration of nerve fibers and maintaining the endothelium of the microvascular bed.Conclusion. The discovered molecular mechanisms of synergism of the studied molecules are of fundamental importance for comprehension of the processes of neuroinflammation regulation and remyelination to prevent diabetic polyneuropathy and other neurodegenerative diseases.